Mutagenesis Induced by Sub-Lethal Doses of Ciprofloxacin: Genotypic and Phenotypic Differences Between the Pseudomonas aeruginosa Strain PA14 and Clinical Isolates - Migliorini, Letícia Busato; Brüggemann, Holger; de Sales, Romario Oliveira; Koga, Paula Célia Mariko; de Souza, Andrea Vieira; Martino, Marines Dalla Valle; Galhardo, Rodrigo S.; Severino, Patricia (Frontiers in Microbiology, 2019)
Bacterial resistance is a severe threat to global public health. Exposure to sub-lethal concentrations has been considered a major driver of mutagenesis leading to antibiotic resistance in clinical settings. Ciprofloxacin is broadly used to treat infections caused by Pseudomonas aeruginosa, whereas increased mutagenesis induced by sub-lethal concentrations of ciprofloxacin has been reported for the reference strain, PAO1, in vitro. In this study we report increased mutagenesis induced by sub-lethal concentrations of ciprofloxacin for another reference strain, PA14-UCBPP, and lower mutagenesis for clinical isolates when compared to the reference strain. This unexpected result may be associated with missense mutations in imuB and recX, involved in adaptive responses, and the presence of Pyocin S2, which were found in all clinical isolates but not in the reference strain genome. The genetic differences between clinical isolates of P. aeruginosa and the reference PA14-UCBPP, often used to study P. aeruginosa phenotypes in vitro, may be involved in reduced mutagenesis under sub-lethal concentrations of CIP, a scenario that should be further explored for the understanding of bacterial fitness in hospital environments. Moreover, we highlight the presence of a complete umuDC operon in a P. aeruginosa clinical isolate. Even though the presence of umuDC did not contribute to a significant increase in mutagenesis, it highlights the dynamic exchange of genetic material between bacterial species in the hospital environment.